2022
DOI: 10.3390/microorganisms10112281
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Klebsiella pneumoniae Species Complex Reveals the Circulation of High-Risk Multidrug-Resistant Pandemic Clones in Human, Animal, and Environmental Sources

Abstract: The Klebsiella species present a remarkable genetic and ecological diversity, being ubiquitous in nature. In particular, the Klebsiella pneumoniae species complex (KpSC) has emerged as a major public health threat in the world, being an interesting model to assess the risk posed by strains recovered from animals and the environment to humans. We therefore performed a genomic surveillance analysis of the KpSC using every public genome in Brazil, aiming to show their local and global relationships, and the conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…The in vitro analyses revealed that Kp196 corresponded to a PDR strain (Table 1), and the cgMLST assigned it to the ST11 pandemic lineage. In spite of the high prevalence of this lineage in Brazil [13], this is the first report of a PDR ST11 in the country. In fact, PDR K. pneumoniae remains rare in Brazil, having only been reported in ST437 and ST258 restricted to the South/Southeast regions [4][5][6].…”
Section: Resultsmentioning
confidence: 69%
“…The in vitro analyses revealed that Kp196 corresponded to a PDR strain (Table 1), and the cgMLST assigned it to the ST11 pandemic lineage. In spite of the high prevalence of this lineage in Brazil [13], this is the first report of a PDR ST11 in the country. In fact, PDR K. pneumoniae remains rare in Brazil, having only been reported in ST437 and ST258 restricted to the South/Southeast regions [4][5][6].…”
Section: Resultsmentioning
confidence: 69%
“…The two strains of K. pneumoniae recovered in this study presented the capsular-type KL105 and Sequence Type 11, previously associated with MDR and virulence determinants (yersiniabactin and colibactin) [ 42 ]. The ST11 KL105 clade has been successfully disseminated in Europe, even circulating in Portuguese hospitals for years [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…species are widely distributed in natural environments, such as soils, waters, plants, etc. [ 62 ]; then, they can be found in samples involving the use of cellulose-based raw materials, such as black liquor. In this way, these species of bacteria may produce enzymes capable of degrading lignin as Klebsiella pneumoniae NX-1 [ 63 ].…”
Section: Discussionmentioning
confidence: 99%